A checklist of names in Alona Baird 1843 (Crustacea: Cladocera: Chydoridae) and their current status: an analysis of the taxonomy of a lump genus - van Damme, Kay; Kotov, Alexey A.; Dumont, Henri J. (Zootaxa, 2010)
We discuss current progress with the revision of Alona Baird, 1843 (Crustacea: Cladocera: Chydoridae), the largest cladoceran lump genus. We present the first inventory of these Aloninae since the 1970’s and include an updated checklist of names, with comments on the current status and position of each taxon. We discuss validity, affinities and synonymy of ca. 240 names, including subspecies and varieties. Recent taxonomic shifts have lead to a better delineation of natural groups in the Aloninae but the Alona puzzle remains incomplete. The majority of taxa are grouped into species-complexes or separate genera. We count 14 Aloninae genera, now considered valid, that were split from Alona. The status of a significant portion remains unclear, due to poor original descriptions and/or loss of type material. Even with detailed morphological descriptions, the phylogenetic position of many Aloninae remains unsettled. Analysis of Alona taxonomy based on the checklist shows historical trends and long periods of instability in the systematics of these micro-crustaceans.